The Impact of Railroad Construction on Community Social Behavior in Marusu District, Maros Regency - Sumandiyar, Adi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The goal of this research is to understand more about how railroad construction affects the social marginalization of individuals in Marusu District, Maros Regency. It used descriptive qualitative research and a case study approach to gather and analyze data on the engagement of all stakeholders in railroad development in Maros Regency. The results showed that the construction of railroads had a good impact on the social behavior of the community, as shown by a shift toward better development and support for government policies. Furthermore, the local population anticipates that the railroad will make their area significantly more advanced, as well as have a favorable impact on social conduct The transition of the local community from an agrarian to a modernist social existence